2012
DOI: 10.1145/2382756.2382797
|View full text |Cite
|
Sign up to set email alerts
|

Verifying android applications using Java PathFinder

Abstract: Mobile application testing is a specialised and complex field. Due to mobile applications' event driven design and mobile runtime environment, there currently exist only a small number of tools to verify these applications. This paper describes the development of JPF-ANDROID, an Android application verification tool. JPF-ANDROID is built on Java Pathfinder, a Java model checking engine. JPF-ANDROID provides a simplified model of the Android framework on which an Android application can run. It then allows the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 4 publications
0
43
0
Order By: Relevance
“…In our previous work [4], [5] we created an Android environment model manually to verify Android applications using JPF. We found that the Android environment is very complex and that components often have references and dependencies on other parts of the system or native libraries without which they would not be setup correctly or they might not run at all.…”
Section: A Environment Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work [4], [5] we created an Android environment model manually to verify Android applications using JPF. We found that the Android environment is very complex and that components often have references and dependencies on other parts of the system or native libraries without which they would not be setup correctly or they might not run at all.…”
Section: A Environment Modelingmentioning
confidence: 99%
“…The first paper entitled "Verifying Android Applications on Java PathFinder" [4], describes the design and implementation of JPF-Android. The second paper, "Execution and Property Specifications for JPF-Android" [5], discusses the syntax of JPF-Android's input script and how events are simulated on the application under test and the addition of Checklists to monitor and verify the execution of Android applications during runtime.…”
Section: Progressmentioning
confidence: 99%
“…In contrast, our approach utilizes information from symbolic execution also when constructing the sequencing of events. Several other symbolic execution tools have been build specifically for Android [14,25]. Related tools for automated testing of web applications, which are also driven by user events, include Apollo [6] for PHP and Kudzu [23] for JavaScript.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, they assume the tester has a valid and complete model of the application. Van der Merwe et al [van der Merwe et al, 2012] present a model checking approach to verify Android applications as an extension to Java PathFinder 1 (JPF). This extension enables the Android AUT's code to be run on the Java Virtual Machine using different event sequences to detect when errors occur.…”
Section: Functional Sustainabilitymentioning
confidence: 99%